Comparison of automatic visual attention in schizophrenia, bipolar disorder, and major depression: Evidence from P1 event‐related component. Issue 6 (10th April 2019) - Spironelli, Chiara; Romeo, Zaira; Maffei, Antonio; Angrilli, Alessandro
Abstract : Aim: The ability to discern commonalities and differences in the neurobiology of functional psychoses represents a key element to unmasking shared vulnerability across different psychiatric conditions. The present study sought to compare the automatic visual attention mechanisms in three psychiatric disorders considered to distribute along the continuum of psychosis severity: schizophrenia (SCZ), bipolar disorder (BD), and major depressive disorder (MDD). To this end, the visual P1 event‐related potential component, a cortical correlate of automatic visual attention, was measured during an ecological task based on visual word pair presentation. Methods: Four samples of participants, 18 SCZ, 20 BD, 28 MDD, and 30 healthy controls, were recruited and submitted to the same procedure and stimuli. The P1 evoked by visual word presentation was recorded through a 38‐electrode electroencephalography cap. Words were presented on a computer screen serially as pairs, and participants had to decide whether they rhymed or not. Results: P1 was larger at posterior sites in SCZ compared with BD, healthy control, and MDD participants. BD patients showed the lowest P1 compared with all other groups. Positive Pearson's correlations were found in SCZ patients between P1 amplitude on left posterior sites and both hallucination severity and worse task performance. Conclusion: The three investigated psychiatric samples showed different automatic visual attention patterns: SCZ patients exhibited the greatest cognitive impairment correlated with the amplitude of P1, MDD patients revealed a normal component, and BD showed a compensated euthymic response different from results of past literature in untreated patients.